Fabric pattern recognition using image processing and AHP method - Al Saleh Manal; Hamdi Thouraya; Jmali Mohamed (AUTEX Research Journal, 2025)
This article aims to provide methods and a system to recognize the woven fabric patterns automatically. Two different approaches were designed to identify the woven patterns in this article: image analysis and the analytic hierarchy process (AHP). In this work, identifying the woven fabric patterns is based on the measurement of some characteristics and parameters that clearly describe and explain the contexture of the fabric. The methods used were essentially pattern recognition and image processing, which aim to numerically calculate four critical parameters which can give a clear idea of the texture and the patterns of fabrics: the continuity of diagonal lines, the section succession in the vertical direction, section succession in the horizontal direction, and isolated blocks. Then, we used the AHP to classify basic weave patterns into three classes representing the fundamental weaves: plain, twill, and satin. Finally, the statistical approach used to evaluate the efficiency of the proposed method concerning classification showed high correlation values between the predicted results and the experimental values. This study has practical implications in the textile industry, especially in the clothing sector. The manufacturers can use the results to automatically identify the woven fabric patterns without using the manual examination method.